Asymptomatic isolated partial hiatal herniation of the pancreas: MDCT evaluation and anatomical explanation: Case report and review of literature. Issue 8 (28th March 2013) - Valente, Tullio; Rossi, Giovanni; Lassandro, Francesco; Rea, Gaetano; Muto, Maurizio
<x xml:space="preserve">Abstract</x> Isolated herniation of the pancreas through a gastroesophageal hiatus is an extremely rare condition, and only one case has been reported in the world literature. We describe a MDCT diagnosis of isolated partial hiatal hernia containing the body of a normal pancreas in an asymptomatic patient, give an anatomical explanation and review the corresponding literature. Clin. Anat. 26:1008–1013, 2013. © 2013 Wiley Periodicals, Inc.